Design and characteristic analysis of CNT thin film thermoacoustic transducer spherical array panel for low intensity focused ultrasound. Issue 5 (4th May 2021) - Zhou, Zhenhuan; Wang, Jinxin; Rong, Dalun; Tong, Zhenzhen; Xu, Xinsheng; Lim, C. W.
Abstract: A novel carbon nanotube (CNT) thin film spherical array panel having excellent thermoacoustic performance and characteristics is proposed to generate low intensity focused ultrasound (LIFU) for noninvasive ultrasound treatment. The proposed spherical array panel has the advantages of easy fabrication, easy device driving, wide-bandwidth, and excellent controllability. A theoretical model for the thermoacoustic transducer array is developed and the corresponding exact solution for the sound pressure field is obtained. To verify the analytical solution, experimental tests are conducted and the comparison between theoretical prediction and experiment results shows excellent agreement. A parametric study concludes that the CNT thin film spherical array panel can generate focused ultrasound beam with adjustable focal region, satisfactory ultrasound intensity, large focal depth, and low side-to-main lobe ratio. Numerical results also indicate that adjusting ultrasound frequency is a feasible and efficient way to control the focal region in LIFU treatment while meeting the requirements with regards to ultrasound intensity, focal depth, and energy efficiency.